DEVELOPMENT RESULTS OF WIRED SPECIALIZED DIGITAL INFORMATION TRANSMISSION SYSTEMS CREATION - Shokalo, V. M.; Tsopa, O. I.; Maslyi, V. V. (International Journal of Computing, 2014)
Conception of special digital information transmission systems (SDITS) creation and results of decision of Ukraine actual scientifically-applied problem of domestic connection apparatus development is presented on the basis of xDSL technologies for the existent wired communication channels. The example of specialized information system development for UMIA is presented in thesis.